Psychosocial Dynamics of The Decision Marry Young In Lombok East NTB Distric (Jurusan Bimbingan dan Konseling Islam, 2022)
In many studies it has been mentioned the impact of marrying young whose dominant proportion is more to the negative side. But in reality, there are still many who do marriage at a young age. The purpose of this study is to uncover the psychosocial dynamics of young marriage decision making both internally and externally and how the two aspects collaborate in providing encouragement for marriage decision making at a young age. The other side of the establishment of the main objectives is the exposure of the causative aspects of marriage on the internal and external sides of the individual. The research conducted uses a descriptive qualitative approach. Where researchers collect data through active interviews openly and closedly as a primary data source method. The focus of the group discusion, observation and understanding of the supporting document evidence as a secondary source. Analyzing the findings in depth, researchers reduce data, present data in the form of narratives, verify data and then draw conclusions. The results of the study found that the decision to marry at a young age is predominantly influenced by external factors rather than the internal side of the individual. The power of external factors exerts an influence on the speed of decision-making to get married. The will on the internal side of the individual is low on the side of interpersonal attraction, the competition side, and the diversion of boring or exhausting activities. However, due to the friction of external factors such as the pressure of high expectations and desires of parents, the fulfillment of family expectations, the economic demands of the family, feelings of anger towards parents or family and the atmosphere of the friendship environment become a source of strength in making decisions to get married even though it is still at a fairly young age.